A Novel Multi-Focus Image Fusion Method Based on Dual-Tree Shearlet Transform. (17th June 2015) - Duan, Chang; Wang, Shuai; Huang, Qihong
In this paper, a multi-focus image fusion method based on Dual-Tree Compactly Supported Shearlet Transform (DT CSST) and Direction Decision Map (DDM) is proposed. DT CSST is a shift invariant modification of conventional Compactly Supported Shearlet Transform (CSST). Based on the mitigation of shift variance of CSST in DT CSST, a clearer fused image could be acquired through the General Image Fusion (GIF) method, and this image is called the initial fused image in this paper. The decision map is determined by the similarity of the initial fused image and the source images. The generation algorithm of the decision map in this paper takes advantage of the directional nature of DT CSST: every direction of the transform generates an initial directional decision map and then yields the final map through vote and smooth steps. This scheme is called DDM in this paper. The proposed method is evaluated by four groups of standard images. The results show that the proposed method is able to improve the quality indices compared with two algorithms which have excellent quality indices.